Project to Enhance Capacity in Social Accountability : On the Local Cambodian Capacity Building Institute - World Bank (Washington, DC, 2013)
The World Bank is financing a program that would enhance the capacity of civil society in Cambodia to promote good governance through social accountability. Reforms have been undertaken in different parts of the world through the practice of social accountability led by civil society actors. The program aims to catalyze a process of learning from the different experiences from other countries as well as from initiatives in Cambodia in order to respond to the challenge identified by the Royal Government of Cambodia in its Rectangular Strategy 2004 good governance is a pre-condition to economic development. The program is designed to enhance and strengthen the practice of social accountability in preparation for the Demand for Good Governance Project (DFGG) of the Royal Government of Cambodia supported by the World Bank. The World Bank Program to Enhance Capacity for Social Accountability (PECSA) aims to assist the people of Cambodia in strengthening governance by expanding social accountability practices through:Enhancing civil society organizations capacity in the use of social accountability tools, adapting international social accountability practices to the Cambodian context, providing sub grants to develop and pilot social accountability practicesPECSA will provide resources for the following program components, training, mentoring and awareness raising, action learning and tool development. A network of social accountability practitioners and a resource center, and monitoring and evaluation as a learning process